The Fork in the Road: Can Science Fiction Survive in Postmodern, Megacorporate America? - Sedgewick, Christina (Science Fiction Studies)
SF has a problem: it has linked its fortunes with a publishing industry whose raison d'être is irrelevant (perhaps even inimical) to the interests and desires of the community of SF readers and writers. Like all postmodern multinational corporate sectors (which it has largely become), the publishing industry seeks to standardize its product and efficiently manage its producers and consumers in order to maximize its profits. Writers and editors have assisted the industry in accomplishing these objectives by subscribing to ‘professionalism’ an ideology that encourages writers to take editors and bookstore-chain executives rather than readers as their primary audience. Since ‘professionals’ place pleasing their employers above their own creativity and vision, professional SF writers censor themselves both consciously and unconsciously in order to meet their employers' perception of the ideological bottom line. The pressures on SF writers to toe this ideological bottom line have become so massive that even consciously resisting writers find them difficult to withstand. The SF community is therefore urged to wrest SF's fate from the hands of the megacorporate publishers and bookstore chains so that diverse tastes can be served by diverse books, something the publishing industry has no interest in doing.